Climate lends a hand - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Abundant and timely rainfall in Rwanda from September 2001 to January 2002 has resulted in a 30% increase in the country s food crop production including maize and cassava. This increase does not mean a lasting improvement of the country s...